IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN KREATIVITAS BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI SMA ISLAM PARLAUNGAN WARU SIDOARJO - Alfirdaus, Jihan Millah; El Yunusi, M. Yusron Maulana; Sulaiman, Sholehuddin (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
The jigsaw type cooperative learning model is unique in increasing student learning creativity, yes that studentsl think critically when the teacher givesn material, and students express and discuss a point of view and experience, obtained by students melalui collective point of view learning,l students are encouraged to be proactive and help each other In mastering the subject matter alGAR achieved maximum achievement. Therefore, solutions and innovations are needed in learning to increase student creativity. This study aims to determine student learning creativity after the application of the jigsaw type cooperative learning model. The method used in this study is qualitative research with observational data collection techniques, interviews and documentation. In this study, the author uses various written sources such as articles, journals, books, and documents that are relevant to the study in the research that the author conducted. The results of this study show that students' learning creativity using the jigsaw type cooperative learning model has increased. So it can be concluded that the jigsaw type cooperative learning model is very effective in increasing student learning results and discussion of the implementation of the jigsaw type cooperative learning model in increasing student learning creativity in fiqh subjects. The jigsaw-type cooperative learning model has an improvement in student learning. Learning creativity in fiqh subjects contributes positively to encouraging students to be active in the learning process. While implementing the jigsaw type cooperative learning model is very important for students to be enthusiastic in the learning process and trained to communicate or argue well.